Formulation and Characterization of Metoclopramide Oral Disintegrating Tablet using Natural Superdisintegrants - Mehta, Priyanshi; Jagwani, Akanksha; Gehalot, Narendra; Joshi, Garvita; Jain, Vikas (Journal of Neonatal Surgery, 2025)
Metoclopramide HCl, a potent dopamine receptor antagonist, is widely used for its antiemetic and prokinetic properties, particularly in the management of nausea, vomiting, and gastroparesis. In this study, a novel approach was employed to formulate orally disintegrating tablets (ODTs) of Metoclopramide HCl using natural superdisintegrants- Plantago ovata and Ocimum basilicum mucilages—aiming to improve patient compliance and enhance drug bioavailability through faster disintegration and dissolution. Tablets were prepared via direct compression method and optimized using a 3² full factorial design. A total of nine formulations were developed and evaluated for key physicochemical parameters including hardness, friability, weight variation, disintegration time, wetting time, water absorption ratio, drug content uniformity, and in vitro drug release. Among all, formulation F06 exhibited superior performance, with rapid dispersion (≈12 seconds), high water absorption (≈80%), and over 89% drug release within 12 minutes, outperforming conventional commercial tablets. IR spectroscopy confirmed the absence of drug-excipient interactions, while short term stability studies validated the formulation's integrity. The study highlights the potential of natural mucilages as effective, biocompatible alternatives to synthetic superdisintegrants in fast-dissolving dosage forms. These findings not only support the pharmaceutical utility of Plantago ovata and Ocimum basilicum mucilages but also pave the way for future research into scale-up, in vivo evaluations, and broader therapeutic applications of natural polymers in ODT technologies..